2006
DOI: 10.1016/j.febslet.2006.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Gain‐ and loss‐of‐function mutations in Zat10 enhance the tolerance of plants to abiotic stress

Abstract: C 2 H 2 -zinc finger proteins that contain the EAR repressor domain are thought to play a key role in modulating the defense response of plants to abiotic stress. Constitutive expression of the C 2 H 2 -EAR zinc finger protein Zat10 in Arabidopsis was found to elevate the expression of reactive oxygen-defense transcripts and to enhance the tolerance of plants to salinity, heat and osmotic stress. Surprisingly, knockout and RNAi mutants of Zat10 were also more tolerant to osmotic and salinity stress. Our result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
363
0
7

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 449 publications
(389 citation statements)
references
References 21 publications
10
363
0
7
Order By: Relevance
“…Several TFs also have well‐defined roles under drought or other abiotic stresses. A mutant in STZ has previously been shown to be more tolerant to sorbitol‐induced stress and salt stress (Mittler et al , 2006), which also corresponds to its mannitol‐tolerant phenotype observed in this study. In contrast, erf98 has been described to be more sensitive to salt stress, which we could not observe under mannitol stress (Zhang et al , 2012).…”
Section: Discussionsupporting
confidence: 86%
“…Several TFs also have well‐defined roles under drought or other abiotic stresses. A mutant in STZ has previously been shown to be more tolerant to sorbitol‐induced stress and salt stress (Mittler et al , 2006), which also corresponds to its mannitol‐tolerant phenotype observed in this study. In contrast, erf98 has been described to be more sensitive to salt stress, which we could not observe under mannitol stress (Zhang et al , 2012).…”
Section: Discussionsupporting
confidence: 86%
“…Transgenics with enhanced or suppressed ZAT10 levels were more tolerant to multiple stresses (Mittler et al, 2006;Rossel et al, 2007). A remarkable tolerance to drought stress has been reported recently in transgenic tobacco plants that express an isopentenyltransferase gene under the control of a drought stress-responsive promoter (Rivero et al, 2007).…”
Section: Ros In Abiotic Stress Responsesmentioning
confidence: 89%
“…We compared the gene expression profiles of the first two expanding leaves of 10-d-old RBRi and Pro35S:XVE plants at 3, 6, 12, and 24 h after induction (HAI) after b-estradiol treatment (see Supplemental Data Set 1 and Supplemental Tables 1 and 2 online). Many early upregulated genes were associated with different types of stress responses (i.e., common stress cluster 12; and particularly included transcription factors involved in the ethylene response, like ETHYLEN RESPONSE FACTOR2 (ERF2) and ERF5, and general stress responses, like RESPONSIVE TO DESICCATION26 (RD26) (Fujita et al, 2004), MYB family transcription factor (TF), SALT TOLERANCE ZINC FINGER (STZ/ZAT10) (Mittler et al, 2006), WRKY33 (Zheng et al, 2006), WRKY40 (Xu et al, 2006), and genes found in the ATTED (Obayashi et al, 2009) coexpression clusters of these factors (see Supplemental Figures 12 and 13 and Supplemental Table 3 online). Thus, it appears that early perturbation of RBR homeostasis is perceived by the leaf as a stress signal, which triggers the upregulation of stress response gene expression.…”
Section: Transcriptome Analysis Of Disrupting Rbr Homeostasis Revealsmentioning
confidence: 99%
“…For a large proportion of the upregulated genes, the response is transient and expression levels normalize or even decrease below wild-type levels at 24 HAI. Prominent among the induced genes are factors involved in the ethylene response, such as ERF2 and ERF5, in general stress responses, such as RD26 ((Fujita et al, 2004), ZAT10 (Mittler et al, 2006), WRKY33 (Zheng et al, 2006), and WRKY40 (Xu et al, 2006), and in responses to reactive oxygen, different types of biotic and abiotic stresses and plant hormones. Furthermore, many of the genes in the ATTED coexpression clusters of these genes are coordinately upregulated (see Supplemental Figure 14 and Supplemental Table 3 online), suggesting that plants either experience stress by RBR downregulation or that a general stress signaling pathway is attenuated by RBR and becomes deregulated by small changes in RBR activity.…”
Section: Gene Expression Regulation By Rbrmentioning
confidence: 99%